Atitudes e crenças de fisioterapeutas em relação à dor lombar crônica - Magalhães, Maurício Oliveira (2011)
Background: Attitudes and beliefs of health care providers about chronic low back pain may be associated with both the advice and treatment that are offered to patients. Moreover these advice and treatments may be associated with therapeutic results as well as with levels of disability and quality of life. The Health Care Providers’s Pain and Impairment Relationship Scale (HC-PAIRS) was developed to assess attitudes and beliefs of health care providers’ about patients with low back pain. The Pain Attitudes and Beliefs Scale for Physiotherapist (PABS-PT) was developed to evaluate the attitudes and beliefs of physical therapists in the development and maintenance of low back pain. There are no clinimetrically tested instruments for measuring attitudes and beliefs of heath care providers with regards to chronic low back pain in Brazil. In addition, it is not known the profile of attitudes and beliefs of Brazilian physiotherapists with regards to patients with chronic low back pain. Objectives: To translate and cross-culturally adapt the Pain Attitudes and Beliefs Scale for Physiotherapists (PABS-PT), to test the clinimetric properties of the Brazilian-Portuguese versions of the Health Care Providers’ Pain and Impairment Relationship Scale (HC-PAIRS) and the PABS-PT and to describe the attitudes and beliefs of Brazilian physiotherapists about the development and maintenance of chronic low back pain. Methods: A total of 100 physiotherapists who routinely treat patients with low back pain in their clinical practice were recruited for the studies presented in this thesis. These physiotherapists completed the HC-PAIRS and PABS-PT twice on a test-retest design with a seven-day interval between the interviews. The following clinimetric properties were calculated: internal consistency, reproducibility (reliability and agreement), construct validity and ceiling and floor effects. In addition, descriptive analyses and linear regression models were built to explore the profile of attitudes and beliefs of these physiotherapists. Results: Both scales demonstrated adequate levels of internal consistency (Cronbach’s alpha ranging from 0.67 to 0.74). The reproducibility ranged from moderate to substantial (Intraclass Correlation Coefficient2, 1 ranging from 0.70 to 0.84; Standard Error of the Measurement ranging from 3.48 to 5.06. Pearson correlation coefficients of the scales ranged from 0.19 to 0.62. No ceiling or floor effects were detected. It was also observed that the average physiotherapists scores were very close to the midpoint of both biomedical (mean = 27.1; SD 7.2) and biopsychosocial factors of the PABS-PT (mean = 24.3; SD 6.3); as well as for the HC-PAIRS (mean = 45.45; SD 10.5). Conclusions: Both Brazilian-Portuguese versions of the PABS-PT and HC-PAIRS have adequate clinimetric properties for measuring attitudes and beliefs of health care providers in patients with chronic low back pain. In addition, we observed that Brazilians physiotherapists were uncertain with regards to biomedical or biopsychosocial orientation for the treatment of patients with chronic low back pain.